Improving access to ART in low-income settings through knowledge transfer: a case study from Zimbabwe. Issue 4 (29th September 2018) - Hammarberg, K; Trounson, A; McBain, J; Matthews, P; Robertson, T; Robertson, F; Magli, C; Mhlanga, T; Makurumure, T; Marechera, F
Abstract: It may be assumed that infertility is not a problem in resource-poor areas where fertility rates are high. However, evidence overwhelmingly shows that childlessness is highly stigmatized in these settings and that women who are unable to bear children suffer significant social and psychological consequences. The World Health Organization has recommended that infertility be considered a global health problem and stated the need for ART to be adapted to low-resource settings. This paper describes a model for improving access to ART in low-resource settings. Experienced ART health professionals from Australia and Italy representing medical science, embryology, nursing and counselling used knowledge transfer to support a clinician, a laboratory scientist and a nurse to establish an ART service in Harare, Zimbabwe. Support and mentorship provided between October 2016 and December 2017 included: hosting the clinician and the embryologist for the new service in established ART clinics for short periods and providing them with dedicated mentorship and training during their stay; funding an experienced embryologist to travel to Zimbabwe (three times) to oversee the setting up of the lab and provide hands-on embryology training; funding a scientist and a nurse to travel to Zimbabwe to troubleshoot and establish protocols for record keeping and psychosocial care; and contributing approximately AUD $15, 000 to the purchase of some equipment. By 31 March 2018, the team at IVF Zimbabwe had performed 166 ART procedures, which at time of writing had resulted in 16 births and 4 ongoing pregnancies. This case study demonstrates that with mentorship and modest financial support from ART experts from high-income settings, health professionals in low-income settings can deliver affordable ART with successful outcomes.